Sharia-Based Digital Economic Policies: A Maqasid Shariah Approach to Achieving Sustainable Development - Erry Fitrya Primadhany; Tekun Suttikornpadee; Maimunah; Muhammad Amin; Rabiatul Adawiyah (Tribakti: Jurnal Pemikiran Keislaman, 2025)
The emergence of the digital economy as a form of technological advancement has created opportunities to support sustainable development. To achieve sustainable development and reduce economic disparities, guidance through economic policies becomes essential. This study aims to explore the potential of Sharia-based digital economic policies in supporting sustainable development by addressing economic inequality. Using a normative jurisprudence approach, this research examines Islamic norms, principles, and evolving doctrines within the digital economy context. The research method applied is normative legal analysis with a conceptual approach. Digital economic policies grounded in Maqasid Shariah are expected to positively impact sustainable development, as they emphasize principles of justice, balance, and collective welfare. Therefore, implementing Sharia-based digital economic policies should be a primary focus within sustainable development efforts. Such policies should encompass the five dimensions of Maqasid Shariah—preserving religion, life, intellect, lineage, and property—and include essential aspects such as digital infrastructure development, comprehensive quality enhancement, strengthening Sharia-based financial systems, and adherence to good governance principles. Thus, Sharia-based digital economic policies hold significant potential to contribute to achieving sustainable development goals.